STUDI AKURASI SOLUSI NUMERIK DAN ANALISIS AERODINAMIKA AIRFOIL NACA SIMETRIK PADA BILANGAN REYNOLDS RENDAH - Ayusyalita, Raras
The performance of airfoils at low Reynolds number has been a research interest in the field of fluid dynamics in recent decades. This attracts higher interest in the development of Unmanned Air Vehicle (UAV) including Micro Air Vehicle (MAV) and the development of utilization of renewable energy, such as wind. Both examples use airfoil as a cross section of the wing and also the profile of wind turbine blades. The airfoil performance in such low Reynolds is highly susceptible to Separation, and allows the formation of Laminar Separation Bubble (LSB) which may affect the aerodynamics and performance of the airfoil. The transition phase from the laminar flow to the turbulent flow precedes the formation of Separation is rather difficult to be modeled using numerical simulations. To find a solution that approximates the real condition, the simulation is carried out using various turbulent models available on ANSYS Fluent 17.1. The purpose of this study is to determine the aerodynamic characteristics and solution of flow over symmetric NACA airfoils in low Reynolds. The study is conducted by numerical simulation using ANSYS 17.1, with Reynolds numbers ranging from 40 x 103 to 150 x 103 and angle of attack in the range of 0o - 15o. The simulation results then compared with experimental data obtained from published studies on the internet, hence the best turbulence model used to show aerodynamic factors and flow phenomena in airfoil at low Reynolds is known. By using the best turbulent model obtained, airfoils on same conditions and dimensions are compared to determine the thickness effects on aerodynamics of symmetrical NACA airfoil.